Ecological stoichiometric of C, N and P of Coilia species - Jiaoyang Duan; Shuang Han; Jing Lai; Yuanyuan Zhang; Zhongjun Hu; Qigen Liu (Aquaculture and Fisheries)
Fish of the Coilia genus play a crucial ecological role by serving as a vital link between marine and freshwater ecosystems. To gain a comprehensive understanding of the ecological patterns, intra-interspecific variations, and potential determinants of Coilia from an ecological stoichiometry perspective, analyzed the concentrations of C, N, and P elements in various types of Coilia, including C. nasus, C. mystus, C. grayii, C. brachygnathus, and C. nasus taihuensis, across the Yangtze River basin. The result shows that: 1) A broad spectrum of eco-stoichiometric patterns within Coilia species, facilitating their adaptation to diverse ecosystems, including seawater and freshwater. Specifically, the C content in Coilia species from 40% to 70%, while N% and P% range between 4%–12% and 0.5%–3%, respectively. 2) Intriguingly, interspecific variations in eco-stoichiometric patterns are predominantly driven by anadromous populations. The anadromous Coilia species, including C. nasus, C. mystus, and C. grayii, exhibit significantly higher C contents and C/N, C/P, and N/P ratios compared to their landlocked and freshwater counterparts (C. nasus taihuensis and C. brachygnathus). However, the trends in N and P content are reversed. 3) Intraspecific differences vary among Coilia species, notably observed in C. nasus taihuensis and C. brachygnathus, where there's minimal correlation with body size. Conversely, C. nasus and C. mystus demonstrate a substantial influence of body size, with increasing fish size associated with higher C content, C/N, C/P, and N/P ratios, while N and P content decrease. This suggests that larger fishes store more energy (C%) in preparation for reproductive migration. In conclusion, this study provides a scientific foundation for comprehending the ecological patterns and intra-interspecific variations in Coilia. Furthermore, it contributes to the application of ecological chemometrics in the study of migratory fish, enriching our understanding of the intricate dynamics within this ecologically significant species.